2013
DOI: 10.1136/bmj.f6571
|View full text |Cite
|
Sign up to set email alerts
|

Hospital readmission performance and patterns of readmission: retrospective cohort study of Medicare admissions

Abstract: Objectives To determine whether high performing hospitals with low 30 day risk standardized readmission rates have a lower proportion of readmissions from specific diagnoses and time periods after admission or instead have a similar distribution of readmission diagnoses and timing to lower performing institutions.Design Retrospective cohort study.Setting Medicare beneficiaries in the United States.Participants Patients aged 65 and older who were readmitted within 30 days after hospital admission for heart fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 48 publications
3
60
1
3
Order By: Relevance
“…For example, when do the 'excess' deaths or readmissions occur at hospitals with high rates compared with those with low rates? Some recent evidence for HF patients suggests that the timing of readmissions within the standard 30-day follow-up period does not vary in Medicare patients, 92 but this is not well established with other populations, patient groups or outcomes.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…For example, when do the 'excess' deaths or readmissions occur at hospitals with high rates compared with those with low rates? Some recent evidence for HF patients suggests that the timing of readmissions within the standard 30-day follow-up period does not vary in Medicare patients, 92 but this is not well established with other populations, patient groups or outcomes.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…A national study conducted by Dharmarajan et al [14] found that readmission diagnoses and timing after admission for heart failure, acute myocardial infarction, or pneumonia do not differ by hospital 30 day risk standardized readmission rates. [14] Both acute myocardial infarction and heart failure are comorbidities included on the LACE index.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Both acute myocardial infarction and heart failure are comorbidities included on the LACE index. [9] The re-…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19] The relevance of the "rehospitalization" topic in the last decade involves two important points: first, the perception that reducing these rates would be a window of opportunity to decrease the waste of resources in the health system and, second, that the hospitalization causes additional damage to the heart and other organs. Hospitals in the United States with high rates of rehospitalization have started to be penalized, which led to a search for evidence-based strategies capable of improving the performance of these instituitions.…”
Section: Introductionmentioning
confidence: 99%